Effect access cavity preparation and taper instrumentation on upper premolar fracture - Stella Fibriyanti Bahry; Bernard O Iskandar; Taufiq Ariwibowo; F Loes Djimahit Sjahruddin (Jurnal Kedokteran Gigi Terpadu, 2023)
Background : Fractures are the most undesirable thing in endodontically treated teeth. The main reason in endodontically treated teeth has a considerable risk for fractures is the loss of tooth structure. Objective : This study aims to determine the effect of access cavity preparation and instrument taper percentage on upper premolar fractures. Material and Methods : Twenty-four upper premolar samples were stored in sterile saline solution. The sample was divided into 2 large groups which were then divided into two groups for each group by random allocation. Twelve contracted endodontic cavity (CEC) preparations and the remaining twelve samples using traditional endodontic cavity (TEC) techniques. Each group was prepared with 6 samples 4% taper instrumentation and 6 samples 8% taper instrumentation. Each sample was irrigated with 5 ml of NaOCl. After that, the sample is tested using a universal testing machine. Result : The CEC group showed a significant reduction in fracture rates compared to the TEC group (p <0.05), but there was no significant difference in the fracture in the tapering instrumentation (p> 0.05). Conclusion : Preparation with the concept of minimally invasive CEC provides better resistance to fractures in the upper premolar while tapering instrumentation does not affect the fracture of the upper premolars.